1994
DOI: 10.1056/nejm199406163302404
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Systemic Oxygen Delivery in the Treatment of Critically Ill Patients

Abstract: The use of dobutamine to boost the cardiac index and systemic oxygen delivery failed to improve the outcome in this heterogeneous group of critically ill patients. Contrary to what might have been expected, our results suggest that in some cases aggressive efforts to increase oxygen consumption may have been detrimental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
472
4
31

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,377 publications
(514 citation statements)
references
References 20 publications
7
472
4
31
Order By: Relevance
“…However, VO 2 only rose in response to increases in O 2 delivery in a subset of patients. When the increased oxygen delivery did not increase VO 2 mortality was extremely high 3. These studies suggest that cytopathic hypoxia (decreased oxygen extraction despite adequate oxygen delivery), rather than decreased oxygen delivery, is a central problem in many critically ill patients 4.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, VO 2 only rose in response to increases in O 2 delivery in a subset of patients. When the increased oxygen delivery did not increase VO 2 mortality was extremely high 3. These studies suggest that cytopathic hypoxia (decreased oxygen extraction despite adequate oxygen delivery), rather than decreased oxygen delivery, is a central problem in many critically ill patients 4.…”
Section: Introductionmentioning
confidence: 94%
“…Whether from impaired oxygen delivery or cytopathic hypoxia, lower VO 2 is associated with increased mortality in sepsis2, 3 and after cardiac arrest 5, 6. The details of exactly how cardiac arrest and resuscitation alter cellular metabolism remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Interventional studies attempting to increase oxygen delivery to supra‐normal levels have indeed not shown beneficial effects on outcomes, and in some cases even the opposite 4. Notably, not all patients and organs are predicted to tolerate relative reductions in blood flow: The renal medulla seems particularly prone to hypoxic injury, especially in patients with pre‐existing capillary flow disturbances.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Apparently, MOF is not the result of insufficient blood supply to individual organs, and attempts to improve outcome by increasing oxygen delivery have yielded conflicting results 4. In the kidney, acute renal failure (ARF) in sepsis is associated with marked reductions of glomerular filtration rate and urine output.…”
mentioning
confidence: 99%
“…Current strategies to increase oxygen delivery may be beneficial in the earliest phases of resuscitation, but this approach may be less effective, or even harmful, in later stages if mitochondrial oxidative phosphorylation is impaired (8). Currently, there is no practical method available to measure mitochondrial dysfunction within vital organs at the bedside.…”
Section: Introductionmentioning
confidence: 99%